Dão-Lalalão (O Devente): invasão da modernidade brasileira no interior de Minas Gerais - Lima, Alexandre Ribeiro de (2012)
This monograph was examined whether the tale Give-Lalalão (The Devente) miner writer João Guimarães Rosa, noting how the representation of an important historical moment for Brazil, the Decade of 1930 until the beginning of 1940, the period in which it is the narrative of the tale selected. The study sought to identify how the writer represented modernity through which the country passed at this historic time. The starting point for research is the main character of the story, noting how his authority is represented in the interior of Brazil at a time when the State was expanding its influence in most regions of the country, this remoteness through technology, politics and authority, with the latter aspect represents the main thrust of the study, through a comparison between what was practiced by the Government throughout the country and what the Laird Soropita did on his farm, this character represents a jagunço to leave this life, due to an inheritance received, and leave violent practices of enforcement authority installs itself on a farm in which he is the sole authority with this, however the time by which the country had been passed when the Government begins the resume of former colonels the authority that belongs to youSoropita, can no longer determine the laws, as it did in the band of irregulars to whom it belonged, but follow the rules state. His farm and the entire region of narrative space, General, suffer the early influences of new technologies coming to the region in historical period indicated. These innovations were coming into the interior of the country not only with objects, but also by the influence of people who came from other places already entered in a culture evolved with modern civil practice, in relation to the custom of the interior of the State of Minas Gerais.